Program Sanitarian Cilik di SD Negeri 011 Samarinda sebagai Sarana Edukasi Pola Perilaku Hidup Bersih dan Sehat pada Masyarakat - Andi Daramusseng; Tri Budi Julianti (Jurnal Pengabdian Pada Masyarakat, 2019)
PROGRAM OF THE LITTLE SANITARIAN IN SAMARINDA ELEMENTARY SCHOOL 011 AS AN EDUCATION FACILITY FOR CLEAN AND HEALTHY LIFESTYLE PATTERNS FOR THE COMMUNITY. Health is a human right and an investment for a productive life. Therefore healthy conditions must always be sought. One effort that can be done by the community is to clean and healthy living behavior. Based on the Health Profile of East Kalimantan, 2015 obtained data of PHBS Household Coverage in Samarinda City by 43%. This shows there is still a lack of understanding of the community about PHBS, especially people living around the Karang Mumus River. Based on this, one urgent program is carried out to improve public understanding of PHBS as a program little sanitarian. This program involves elementary school-age children because at that age; it is a golden age to instill clean and healthy living behavior values so that it has the potential as a change agent to promote PHBS. This program was implemented in Elementary School 011 Samarinda through the provision of clean and healthy living behavior materials and practices to 90 students in class 3 and 4. The selection of Little sanitarian cadres was made through the selection of real understanding that had been given. The results of this activity were selected six cadres of little sanitarian, namely 1 class 3 and 5 class 4. This activity is expected to continue with the guidance of Little Sanitarian cadres and cooperation with related parties to hold the movement of Little Sanitarian.